Inverse Optimization: Theory and Applications - Chan, Timothy C. Y.; Mahmood, Rafid; Zhu, Ian Yihang (Operations Research, 2025)
A Review of Inverse Optimization In recent years, there has been an explosion of interest in the mathematics and applications of inverse optimization. Unlike traditional optimization, which seeks to compute optimal decisions given an objective and constraints, inverse optimization takes decisions as input and determines an objective and/or constraints that render these decisions approximately or exactly optimal. In “Inverse Optimization: Theory and Applications,” Chan, Rafid, and Zhu provide a comprehensive review of both the methodological and application-oriented literature. Specifically, the authors consolidate various model properties, reformulation techniques, and computational methods of different classes of inverse optimization problems. The authors also review a wide range of application areas that include, but are not limited to, transportation, logistics, healthcare, and energy systems. The paper concludes with several major directions for future research.